Appraising the Effects of Social Media Information during the Electioneering Period in Nigeria - Azubuike, Chieme; Nwaubeta, Nnennaya Grace (POPULIKA, 2025)
Information is very essential especially during election period that is why candidates and voters utilize it to spread information because of how viable it is in circulating information. The study sought amongst others to examine the effects; negative or positive of social media information circulation in an election period in Nigeria. It was anchored on the Mediatization of politics theory. The descriptive survey research design was used in this investigation. The residents of Owerri metropolis constitute the population of this study. The multistage sampling technique was used. Copies of questionnaire were given out to residents of Owerri Metropolis. The researchers purposefully selected two communities each from local government areas that make up the Owerri metropolis. It was revealed that many of the respondents with a mean average of 2.7 agrees that different social media outlet within their reach and beyond plays key roles in the journey of a smooth, people oriented and positive driven transition of power during and after elections ensuring that the country does not go haywire because of political differences. It was recommended that media role as an advocate of the people in the quest for peaceful pre and post-election period in Nigeria as such should transcend to personal social media users. Keywords: Social Media; Election; Information; Political.